The interplay of type 2 immunity, helminth infection and the microbiota in regulating metabolism - Mati Moyat; Gillian Coakley; Nicola L Harris (Clinical & Translational Immunology, 2019)
Abstract Type 2 immunity has recently emerged as a critical player in metabolic status, with numerous studies investigating the role of type 2 immune cells within adipose tissue. Metabolic dysfunction is often characterised as a low‐grade or chronic inflammatory state within tissues, and type 2 immunity may facilitate a return to metabolic homeostasis. A complex network of type 2 resident cells including M2 macrophages, eosinophils and ILC2s has been identified within adipose tissue. Although the effector cells in this equilibrium have not been clearly identified, any alteration of the type 2 microenvironment resulted in an altered metabolic state. Historically, the type 2 immune response has been associated with helminth infection. The type 2 immune response drives host resistance and plays an important role in promoting tissue repair following the migration of helminth larvae through tissues. Although helminths are largely eradicated in developed countries, infection rates remain high in poor communities within the developing world. Interestingly, there is strong evidence that helminth infection is inversely correlated with autoimmune or inflammatory disorders. Recently, an increasing amount of epidemiological and field studies suggest that it could be the same for obesity and metabolic syndrome. In the current review, we summarise the literature linking type 2 immunity to improved adipose tissue function. We then discuss more recent evidence indicating that helminth infection can provide protection against metabolic syndrome. Lastly, we explore the possible contributions of altered nutrient uptake, adipose tissue function and/or the intestinal microbiota with the ability of helminths to alter metabolic status.